The moderating role of income inequality in the relationship between sustainable development and geopolitical risk - Phan, Thi Hang Nga; Nguyen, Vu Duy; Tran, Khanh Quynh; Trinh, Thi Lien; Do , Nguyen Thi My Dung; Phan, Thuy Duong (Journal of Finance - Marketing Research, 2026)
This study investigates the moderating role of income inequality (INEQ) in the relationship between geopolitical risk (GPR) and sustainable development (SD). Using Bayesian regression techniques on panel data from 27 countries over the period 2010–2021, the study provides robust empirical evidence on how INEQ and GPR jointly shape SD outcomes. The results indicate that INEQ exerts a statistically significant and negative effect on SD, with a posterior probability of 100%. This finding suggests that unequal income distribution weakens human capital formation, institutional quality, and social consensus for environmental policies. In contrast, GPR is found to positively influence SD within the sample, potentially reflecting short-term economic–environmental adjustment effects, whereby conflicts reduce growth, investment, and energy consumption, leading to temporary environmental improvements. However, the interaction term between INEQ and GPR is negative and highly significant (posterior probability of 99.96%), indicating that inequality substantially weakens the positive impact of GPR on SD. In highly unequal societies, adaptive capacity to external shocks is more limited, thereby undermining sustainable outcomes. Additionally, green innovation, urbanization, trade openness, government size, and renewable energy consumption are found to promote SD, while extensive GDP growth, FDI inflows, population growth, and reliance on natural resources exert adverse effects.